Design of Augmented Reality–Based Learning Media for Islamic Religious Education Material on Replies to Non-Believers at Muhammadiyah 12 GKB Gresik Middle School - Novi Nazilatur Rohmah (International Journal of Islamic Educational Research, 2025)
In supporting the learning process, teachers often use videos on YouTube, Instagram, and TikTok for learning media nowadays. One that can be used for learning media is Augmented Reality. Augmented Reality in the world of education has not been implemented and applied as a supporting medium for interactive education in schools, because no educational institution has implemented it as a mandatory media that functions as a learning tool. Muhammadiyah 12 GKB Gresik Middle School has a Digital Technology Class Program that strives to provide a forum for teachers and students to always actively use technology in learning in class and outside the classroom. With the material Reply for unbelievers, it is hoped that it can be visualized through Augmented Reality. Based on the background above, the author tries to explain the main statement (1) how to design an effective, efficient, and interesting Augmented Reality learning model for 8th grade students of the Quranic material, Surah Al Fajr, reply for unbelievers. (2) what are the advantages and disadvantages of the Augmented Reality learning media design. This study aims to describe the design of the Augmented Reality learning model so that it is effective, efficient, and interesting. As well as describing the advantages and disadvantages of Augmented Reality learning media design so that it can be effective, efficient and interesting for students. The research method used by researchers uses the Research and Development method by adopting the ADDIE development model in the first two steps: Analysis and Design. The results of the needs analysis on the use of Augmented Reality (AR) media in learning replies for non-believers, this is effective, efficient and interesting if used in the learning process for students, and is needed, especially in learning replies for non-believers.